Institutional Capacity and COVID-19 Response Among Romanian Public Health Directorates: An Exploratory Cross-Sectional Analysis of 20 Jurisdictions - Lenuța Silvia Nicoruț; Timea Claudia Ghitea; Rareș Cristian Daina; Eleia Zina Csákvári; Mădălina Diana Fehér; László Fehér; Lucia Georgeta Daina (COVID, 2026)
Background: Transparent measurement is essential when organizational capacity is compared across public health institutions. The supplied analytic dataset did not contain repeated annual scores or indicator-level evidence for the previously proposed five-domain maturity model. We therefore conducted a reproducible cross-sectional analysis limited to the variables available in the dataset. Methods: Twenty Romanian public health directorates (PHDs)—10 in counties with a university medical center (CU) and 10 in counties without one (FU)—were compared using structural indicators, eight binary COVID-19 re-sponse measures, and a composite capacity–response index. The index was the equally weighted arithmetic mean of four sample-normalized components: employees per 100,000 inhabitants, budget per capita, previous-crisis experience, and the number of documented COVID-19 measures. Results are presented as medians and interquartile ranges. Mann–Whitney U and Fisher exact tests were used, with Holm correction within comparison families. Results: The composite index was higher in CU than FU institutions (55.0 [38.0–66.3] vs. 22.0 [19.3–31.3]; U = 93.0; p = 0.0013; Holm-adjusted p = 0.0077; rank-biserial r = 0.86). CU institutions also had larger populations, more employees, larger total budgets, higher per capita budgets, more previous-crisis experience, and more documented response measures. Employees per 100,000 inhabitants did not differ significantly. After multiplicity correction, vaccination-center involvement and communication/education were more frequently documented in the CU group. Digital platforms were recorded for only two institutions and cannot be interpreted as a digital-maturity domain. Conclusions: The available data support descriptive evidence of institutional disparities associated with the university-center context, but they do not support causal inference or validation of a maturity model. The composite index should be treated as an exploratory, sample-dependent benchmarking measure pending prospective instrument development, documented scoring rules, independent assessment, and external criterion validation. Its group difference largely reflects the four constituent components, which should remain the primary basis for interpretation.